2020
DOI: 10.1002/jbm.a.36894
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive materials for in vitro cardiac microtissue engineering

Abstract: Cardiac tissue engineering, a fairly new concept in cardiovascular research, could substantially improve our success in both in vitro modeling of cardiac microtissue and in vivo cardiac regenerative medicine. To a large extent, this success was attributed to mechanical as well as electrical properties of cardiac‐designated biomaterials which inherit the fundamental characteristics of a native myocardial extracellular matrix. Large efforts have been made toward designation and construction of these scaffolds wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 52 publications
0
31
0
1
Order By: Relevance
“…biomaterials have been tested for their use as scaffold to provide three‐dimensional microenvironment for supporting the growth and survival of cardiomyocytes (CMs) (Gil‐Castell et al, 2020; Kaiser et al, 2019; Pushp & Ferreira, Cabral, et al, 2017; Pushp et al, 2019; Rachel et al, 2020). Properties such as mechanical strength, cyto‐compactibility, electrical conductivity, porosity, high surface to mass ratio, high oxygen carrying potential, and so forth are important in the selection of biomaterial for fabricating scaffolds for CTE (Baei et al, 2020; Nikolova & Chavali, 2019; Zhang et al, 2019). In addition, to be used as cardiac patch, the tensile strength of the biomaterials should have a Young's modulus of 0.02–0.5 MPa to resemble those of the native human heart (Reis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…biomaterials have been tested for their use as scaffold to provide three‐dimensional microenvironment for supporting the growth and survival of cardiomyocytes (CMs) (Gil‐Castell et al, 2020; Kaiser et al, 2019; Pushp & Ferreira, Cabral, et al, 2017; Pushp et al, 2019; Rachel et al, 2020). Properties such as mechanical strength, cyto‐compactibility, electrical conductivity, porosity, high surface to mass ratio, high oxygen carrying potential, and so forth are important in the selection of biomaterial for fabricating scaffolds for CTE (Baei et al, 2020; Nikolova & Chavali, 2019; Zhang et al, 2019). In addition, to be used as cardiac patch, the tensile strength of the biomaterials should have a Young's modulus of 0.02–0.5 MPa to resemble those of the native human heart (Reis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, electrically conductive scaffolds for cardiac tissue engineering has been an important and innovative field in ensuring proper and mature electrical activity of engineered tissue. A variety of materials such as gold nanoparticles, carbon nanotubes, graphene, polypyrrole and polyaniline have been utilized; these materials and their impact on engineered cardiac tissue is reviewed in great detail by Baei et al [ 273 ].…”
Section: New Directionsmentioning
confidence: 99%
“…It has been applicated in the construction of different engineered tissues like cornea (37), skin (38), oral mucosa (24) and peripheral nerve (39) among others, and they have shown that the nanostructuration and cross-linking techniques improved the biomechanical and structural properties of different biomaterials. For cardiac tissue engineering, it is crucial the development of electrically conductive hydrogels to achieve the spontaneous beating behaviour of the heart, in order to accomplished the functional regeneration (8,40).…”
Section: B) Hydrogelsmentioning
confidence: 99%